The Influence of Business Expectations, Performance Expectations, Business Expectations, and Social Influences on Interest in Using BRImo (BRI Mobile) - Partini, Partini; Wijianto, Wijianto; Hartono, Sri (PT. Anagata Sembagi Education, 2025)
This study aims to determine the effect of performance expectancy, effort expectancy and social influences on behavioral intention of BRImo (BRI Mobile) at BRI Unit Karangrejo Magetan. The data used are primary data obtained from questionnaires. Data analysis used is t test, F test and coefficient of determination. The results of this study indicate that performance expectancy has a partial effect on behavioral intention of BRImo at BRI Unit Karangrejo Magetan. This means that high performance expectations will trigger BRImo's behavioral intention for their daily transactions. Business expectancy has a partial effect on behavioral intention BRImo at BRI Unit Karangrejo Magetan. This means that the better the effort expectancy, the behavioral intention of BRImo by customers will also increase. Social influence partially affects the behavioral intention of BRImo at BRI Unit Karangrejo Magetan. This means that a large social influence will result in greater customer behavioral intention in transactions using BRImo.